DISPUTE RESOLUTION OF DEFAULT OF CV KARYA PUTRA BERSAMA IN COAL PROCUREMENT AGREEMENT BETWEEN PT. TJIWI CHEMICAL PAPER MILL, TBK. AND PT. INDAH KIAT PULP & PAPER, TBK. - Indrawati, Titik; Astutik, Sri; Subekti (Awang Long Law Review, 2025)
Contractual disputes due to breaches often occur in business relationships, including the case between CV. Karya Putra Bersama and the plaintiff. This study aims to analyze the legal basis and resolution process of breach of contract disputes and their impact on the parties. The research questions include the causes of the breach, dispute resolution steps, and court decisions. The study employs a normative juridical approach by analyzing contract documents, legal facts, and court rulings. Findings indicate that the defendant breached the contract due to delayed deliveries and violations of contractual commitments, leading to a court ruling requiring the defendant to pay penalties and damages. Furthermore, non-litigation efforts such as legal notices failed due to the defendant's lack of goodwill. This study emphasizes the importance of detailed contract drafting and optimizing non-litigation dispute resolution to prevent legal and financial losses.